Effects of esophageal acid infusion vs mosapride on distension‐induced secondary peristalsis in humans - Lei, Wei‐Yi; Hung, Jui‐Sheng; Yi, Chih‐Hsun; Liu, Tso‐Tsai; Wong, Ming‐Wun; Chen, Chien‐Lin (The Kaohsiung journal of medical sciences, 2019)
Secondary peristalsis contributes to the clearance of the refluxate from the esophagus. Acute administration of 5‐hydroxytryptamine 4 (5‐HT4) receptors agonist, mosapride or esophageal infusion of hydrochloric acid (HCl) facilitates secondary peristalsis. The aim of this study was to determine whether esophageal acid infusion and administration of mosapride had different effects on secondary peristalsis. Secondary peristalsis was performed with esophageal distension with rapid and slow air injections in 16 healthy subjects. We performed two separate sessions with HCl (0.1 N) and 40 mg oral mosapride to compare their influence on secondary peristaltic parameters. The threshold volume of secondary peristalsis was significantly lower with HCl infusion than mosapride (P = 0.01) by slow air injections. The threshold volume to generate secondary peristalsis was significantly lower with HCl infusion than mosapride (P = 0.002) by rapid air injections. More secondary peristalsis was trigged by rapid air injections after HCl infusion than mosapride (P = 0.003). Infusion of HCl or mosapride administration has similar effects on peristaltic wave amplitude and duration of primary and secondary peristalsis. Acute esophageal acid infusion can induce greater mechanosensitivity to distension‐induced secondary peristalsis than 5‐HT4 receptors agonist mosapride. The data suggest that acid‐sensitive afferents are more likely to contribute to sensory modulation of esophageal secondary peristalsis; however, the motility aspects of secondary peristalsis are comparable between acute esophageal acidification and 5‐HT4 receptors activation via mosapride.